Risk Factors of Stunting in Children Age 24-59 Months Old - La Ode Alifariki; La Rangki; Haryati Haryati; Rahmawati Rahmawati; Sukurni Sukurni; Wa Ode Salma (Media Keperawatan Indonesia, 2020)
Stunting is a short and very short body state that exceeds the Z-Score -2 SD deficit below the median length or height, as measured by height by age or length by age (TB / U or PB / U). Many factors affect the incidence of stunting in toddlers aged 24-59 months. The aim of the study is to determine the determinants of the incidence of stunting in infants aged 24-59 months. This type of research is observational analytic using a case-control design. The study population was all mothers who have children aged 24-59 months in the working area of Puuwatu Health Center, Kendari City. The number of sample cases as many as 35 people while the number of control samples as many as 72 people with a sample comparison of 1 case: 2 controls so that the total sample size of 108 people, obtained through purposive sampling. The results showed that mothers who had a height of <150 cm had a risk of 2.6 times having a toddler suffering from stunting compared to mothers who had a height of ≥ 150 cm. Determinants of stunting proxies in the working area of Puuwatu Health Center, Kendari City was maternal height with Exp value = 0.386.